Biologically-Inspired Radar and Sonar : Lessons from nature - Balleri, Alessio; Griffiths, Hugh; Baker, Chris (IET radar, sonar, navigation and avionics series., 2017)
The following topics are dealt with: biologically-inspired radar; biologically-inspired sonar; biosonar-inspired signal processing; acoustic imaging; matched filter; air-coupled sonar systems; cognitive sensor; target tracking; human echolocation; polarization tensors and object recognition.